2019
DOI: 10.3390/jcm8081264
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Rehabilitation Reduces Subjective Fatigue in COPD: A Responder Analysis

Abstract: To date, it remains unknown which patients report a clinically-relevant improvement in fatigue following pulmonary rehabilitation (PR). The purpose of this study was to identify and characterize these responders. Demographics, lung function, anxiety (anxiety subscale of the 90-item symptom checklist (SCL-90-A)), depression (Beck depression inventory for primary care (BDI-PC)), exercise tolerance (six-minute walking distance test (6MWD)), and health status (Nijmegen clinical screening instrument (NCSI)) were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 53 publications
3
20
0
Order By: Relevance
“…Severe fatigue has been observed frequently in patients with chronic obstructive pulmonary disease (COPD) (ranging between 41 to 75%) [49][50][51], asthma (62%) [52], or cancer survivors (range from 7% to 52%) [53]. The current findings of severe fatigue of 48% and 69% in patients with IPF or sarcoidosis, respectively, fit well.…”
Section: Severe Fatigue In Patients With Ipf or Sarcoidosissupporting
confidence: 62%
“…Severe fatigue has been observed frequently in patients with chronic obstructive pulmonary disease (COPD) (ranging between 41 to 75%) [49][50][51], asthma (62%) [52], or cancer survivors (range from 7% to 52%) [53]. The current findings of severe fatigue of 48% and 69% in patients with IPF or sarcoidosis, respectively, fit well.…”
Section: Severe Fatigue In Patients With Ipf or Sarcoidosissupporting
confidence: 62%
“…However, results from the multivariate linear regression analysis revealed that only 11% of the changes in V O2peak were explained by the baseline fatigue score. Interestingly, our results were in line with a recent published prospective responder analysis of 446 COPD patients with fatigue following a 12 week interdisciplinary PR program (96).…”
Section: Pulmonary Rehabilitation and The Impact On Exercise Capacitysupporting
confidence: 92%
“…This extrapulmonary sign is believed to be “the subjective perception of fatigue coupled with exhaustion and a lack of power occurring every day” ( 29 - 31 ). Fatigue is capable of significantly impacting not only the physical but also the mental well-being of patients with COPD, which is usually linked to anxiety, depression, and dyspnea ( 32 , 33 ). A four-year observational study investigating fatigue in patients with COPD confirmed this perspective ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations have revealed an improvement in fatigue among COPD patients following PR and that this improvement is likely attributed to PR addressing the risk factors that lead to fatigue, such as anxiety, depression, and dyspnea ( 33 ). In a systematic review, three randomized controlled trials (n=269) of comprehensive PR led to reductions in short-term anxiety and depression ( 35 ).…”
Section: Introductionmentioning
confidence: 99%